(untitled) (Sir Salimullah Medical College Journal, 2022)
Background: Sepsis is one of the most common causes of mortality and morbidity in the intensive care unit (ICU). Objective: This study was done to evaluate eosinopenia as a marker of sepsis in intensive care unit patients. Materials and Methods: This cross sectional study was carried out in the Department of Clinical Pathology, Bangabandhu Sheikh Mujib Medical University, Dhaka . AEC was done by automated cell counter and rechecked manually microscopically. Observations and Results: In this study 74 suspected case of sepsis were enrolled from intensive care unit, BSMMU, Dhaka. To evaluate the usefulness of AEC for predicting significant sepsis the area under the ROC curve was analyzed. The area under ROC curve was 0.765 in current study. At the cut off valve of AEC < 40 cell/cu mm, the sensitivity and specificity of AEC for diagnosis of sepsis was 72.5% and 61.8% respectively. Conclusion: This present data revealed that decreased absolute eosinophil count was significantly associated with sepsis. So eosinopenia may be a reliable marker for early diagnosis of sepsis. Sir Salimullah Med Coll J 2022; 30: 175-179